Quantitative analysis of DNA-Dox diffusion kinetics in a microfluidic device using the fluorescence lifetime imaging microscopy method. (27th October 2020) - Ren, Sheng; Liu, Liwei; Zhao, Yihua; Lin, Fangrui; Hu, Rui; Yi, Rongxing; Shen, Binglin; Qu, Junle
Abstract: We used a fluorescence lifetime imaging microscopy combined with a microfluidic mixer to study the kinetics of doxorubicin hydrochloride (Dox) diffusion into DNA. The mixing process in the microchannel model was simulated using COMSOL. According to the change of fluorescence lifetime before and after the binding of Dox to DNA, the fluorescence quenching effect of DNA on Dox was obtained both temporally and spatially, and the kinetic information was analyzed from imaging experiments. The experimental results show good agreement with the computational fluid dynamics simulation, and this method could be used to analyze the diffusion process of drug molecules.